Reflection Of The Kazakh Traditional Culture In Language - Atabayeva, Mereke; Bissenbayeva, Alua Nazarbekova, Aigerim Bogenbayeva, Gulnafis Yerkegaliyeva, Meruyert (Opción, 2019)
The research in contemporary linguistics gives importance to the consideration of language as a cultural phenomenon, mirror of national outlook, and reflection of national culture via comparative qualitative research methods. As a result, it is easier to define the cultural data, which appeared in different periods of the history of a particular era on the basis of social sources rather than on ancient relics. In conclusion, the content of centuries-old traditional culture of a nomadic life shows the depth of the creative force and richness of ethno cultural semantics.